6t+3(5t-4)=12(2t)-5

Simple and best practice solution for 6t+3(5t-4)=12(2t)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t+3(5t-4)=12(2t)-5 equation:


Simplifying
6t + 3(5t + -4) = 12(2t) + -5

Reorder the terms:
6t + 3(-4 + 5t) = 12(2t) + -5
6t + (-4 * 3 + 5t * 3) = 12(2t) + -5
6t + (-12 + 15t) = 12(2t) + -5

Reorder the terms:
-12 + 6t + 15t = 12(2t) + -5

Combine like terms: 6t + 15t = 21t
-12 + 21t = 12(2t) + -5

Remove parenthesis around (2t)
-12 + 21t = 12 * 2t + -5

Multiply 12 * 2
-12 + 21t = 24t + -5

Reorder the terms:
-12 + 21t = -5 + 24t

Solving
-12 + 21t = -5 + 24t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-24t' to each side of the equation.
-12 + 21t + -24t = -5 + 24t + -24t

Combine like terms: 21t + -24t = -3t
-12 + -3t = -5 + 24t + -24t

Combine like terms: 24t + -24t = 0
-12 + -3t = -5 + 0
-12 + -3t = -5

Add '12' to each side of the equation.
-12 + 12 + -3t = -5 + 12

Combine like terms: -12 + 12 = 0
0 + -3t = -5 + 12
-3t = -5 + 12

Combine like terms: -5 + 12 = 7
-3t = 7

Divide each side by '-3'.
t = -2.333333333

Simplifying
t = -2.333333333

See similar equations:

| x^2-2x=-15 | | 6(2k+1)-21=21 | | 1/3(n+1)=1/(3-5) | | y=(4y^2-x^2)/(4xy) | | 9-1a=5.66-1a | | Ln(12x)-ln(3)=5 | | 111y=37 | | K=3+5-2+6-(-5) | | 11=2-3v | | 85=.5x(17) | | 15m-4(2m-6)=38 | | 3*3*3-(31-2*3)= | | -2(3-7x)=22 | | 15-7(x-2)=1 | | (2sin2x)/x | | u^2-32u+31=0 | | 10x+9(3)=8 | | 1/4d_ | | f(x)=ln(81sin^2x) | | 3+4x=13+9x | | 2a^3b^0/c^2)-3 | | An=n^2+3n | | Tan^2x-5tanx-6=0 | | 2y=-3x+8 | | -4(7x+1)=-312 | | -5=-20+-25 | | 12x^2-132x+252=0 | | 30=7+N-4+8 | | 40=-2(23-y)+3(y-3) | | -8=17+6z | | 6(x+6)=-9+3x | | 7=3(23-x)+2(x-2) |

Equations solver categories